Relevance of Financial Performance and Good Corporate Governance Determinant of Sustainaibility Corporate Social Responsibility Disclousure in Islamic Bank in Indonesia - Fitriyah Fitriyah; Ulfi Oktaviana Oktaviana (International Journal of Nusantara Islam, 2013)
The purpose of the paper is to investigate role of the financial performance, ownership structure and number of syari'a supervisory board of Islamic banks in Indonesia on the sustainability of corporate social responsibilities (CSR) disclosure. Ownership structure and number of syari'a supervisory board of Islamic banks as proxy of implementation good corporate governance (GCG). There are seven (7) fully fledge Islamic banks in Indonesia. This study uses logic regression to test empirically whether the CSR is highly influenced by the factors identified earlier. Evidence was found that size, ROA and leverage do not have significant role in corporate social responsibilities (CSR) disclosure. Specifically, the results infer the fact that the CSR disclosures are significant and positively associated to bank size and ownership structure only. The result of the study has confirms the hypothesis that bank size and ROA has positive associated with CSR disclosure. This suggested that large and profitable banks have more resources to devote to social activities. Leverage negatively influences the disclosure of CSR. Thus, lowly leveraged banks will tend to make larger donations than highly leveraged banks. Ownership structure and number of syari'a supervisory board of Islamic banks have positive associated to CSR disclosure. These results also confirm the predictions that good corporate governance mechanism lead to the greater monitoring and thereby greater CSR disclosure.